TERF2 gene expression in childhood acute lymphoblastic leukaemia / Lelamekala Vengidasan - Vengidasan, Lelamekala (2011)
Advances in the understanding of cell biology in childhood acute lymphoblastic leukemia (cALL) have led to sophisticated risk-stratification based therapeutic interventions targeting individual patients. Despite these advances, approximately 10-20% of children with ALL still relapse. Thus, identification of new prognostic indicators will allow for better targeted treatment. TERF2, one of the main components of the shelterin complex (telosome), has been found to be over-expressed in a variety of epithelial malignancies, including lung, skin and breast cancer. This study aims to investigate the level of expression of TERF2 in pediatric ALL and in different cALL patient subgroups and its potential as a prognostic marker in such patients. Diagnostic bone marrow samples were obtained from 72 paediatric patients treated at the University Malaya Medical Centre (UMMC) under the Malaysia-Singapore ALL 2003 study protocol. Expression of TERF2 was measured via real time quantitative PCR using cDNA synthesized from the samples described above. Results were standardized using Β2M transcripts as the internal control and HL60 as the calibrator. Relative quantification of gene expression was calculated by using the delta delta Ct method.